TRIPLE C (CENTRALIZE AND COMPREHENSIVE CONCEPT) SEBAGAI USAHA STRATEGIS PENERAPAN E-MONEY INDONESIA - Ramdani, Dandy Dwi; Gandana, Ratna Suryani; Setyamarta, Natasya; Aulina, Lili (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2014)
Using cash money as a transaction media has many weaknesses, there are, the transaction will no longer efisien and easy, the costs to make e-money is really expensive, and so many fake cash money that are distributed. To prevent that weaknesses, since 2010 Bank Indonesia has create Less Cash Society program to promote the use of non-cash money to do the transaction, like e-money. Bank Indonesia give franchise to the Bank in Indonesia to produce e-money. However, because of many kinds of e-money is produced by many Banks, the society confuse in using and understanding it. Thatâs why to solve this solution, the writer create the Triple C (Centralize and Comprehensive Concept) as a strategic effort to apply e-money Indonesia. We use the method of literarute study, interview, and observation. The result of Triple C are e-money system that is centralized in Bank Indonesia and e-money smart societies, as the result e-money Indonesia can be implemented as fast and comprehensive.Keywords: transaction, money, e-money, bank, citizen